2020
DOI: 10.1186/s12894-020-00761-9
|View full text |Cite
|
Sign up to set email alerts
|

The impact of lower urinary tract symptoms on the quality of life during pregnancy: a cross-sectional study from Palestine

Abstract: Background Lower urinary tract symptoms (LUTS) are prevalent among pregnant women. Several articles show the impact of LUTS on pregnant women’s quality of life (QoL). This study was designed to examine the impact of non-pathological LUTS on QoL among pregnant Palestinian women. Methods A cross-sectional, hospital-based study was conducted on women who were pregnant and receiving regular antenatal care at the obstetrics and gynecology clinic in Rafi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 41 publications
(47 reference statements)
1
15
0
Order By: Relevance
“…Finally, patient age, multiparity, obesity, and stage of pregnancy are all factors that, according to our study, influence LUTS during pregnancy. Therefore, education should be available to all women of childbearing age, to enable them to modify lifestyle risk factors or at least quickly recognise symptoms early during pregnancy to avoid the harmful effects, particularly on QoL [16,30].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, patient age, multiparity, obesity, and stage of pregnancy are all factors that, according to our study, influence LUTS during pregnancy. Therefore, education should be available to all women of childbearing age, to enable them to modify lifestyle risk factors or at least quickly recognise symptoms early during pregnancy to avoid the harmful effects, particularly on QoL [16,30].…”
Section: Discussionmentioning
confidence: 99%
“…LUTS and related underlying conditions can cause major disruption to a pregnant female's daily activities and interfere with their work, exercise, and social life [10][11][12][13][14][15]. Furthermore, LUTS can negatively impact the quality of life (QoL) of pregnant women [15,16]. Thus, several strategies should be enacted during the antenatal period to identify LUTS.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, it has been indicated that HRQoL can be considered as one of the most important components of the quality of medical and health care [13]. Few studies assessed HRQoL in Palestinian patients with other medical conditions rather than RA [14][15][16][17][18][19][20][21], and no study has assessed patients' disability in a specific disease. Despite the importance of HRQoL and the degree of disability in patients with RA, no previous studies have been carried out to the best of our knowledge to determine HRQoL or disability in patients with RA in Palestine.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have reported negative impact of OAB on the HRQoL that can be translated as negative effects on the physical, social, and psychological well-being [9]. OAB can also have negative interference with the daily activities of the affected individuals [9,10]. Additionally, OAB affects the patients' relationships with spouse/partner, family, and friends.…”
Section: Introductionmentioning
confidence: 99%